Implementation Of the Minister of Social Regulation Number 1 of 2018 Concerning the Harapan Household Program (PKH) (Case Study in Talang Keramat Village Talang Kelapa District Banyuasin Regency) - Fahlevi, Arya Halbadika (Utan Kayu Publishing, 2022)
The problem of poverty is one of the issues that hinder development. Poverty is a central problem that must be addressed immediately in an effort to realize the national goals as stated in the Preamble to the 1945 Constitution, namely protecting the entire Indonesian nation and the entire homeland of Indonesia, promoting public welfare, educating the nation's life and participating in carrying out world order based on independence, lasting peace and social justice. The research method used is a qualitative method. Data was collected by means of observation, interviews, documentation, and literature study. Data analysis is carried out by means of data reduction, data presentation, drawing conclusions and verification The results of the research and discussion, the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program (PKH) carried out in Talang Keramat Village, Talang Kelapa District, Banyuasin Regency has been carried out well because communication has been created well, implementing officers have carried out their obligations with full responsibility. responsibility, the existing bureaucratic structure can also be understood by the community, this makes the implementation of PKH effective. However, there are several problems, firstly, the Kelurahan is only a facilitator, secondly, no budget funds have been received by the output in the implementation of PKH and the third is data collection that is not relevant to people's lives. Abstrak: Masalah kemiskinan merupakan salah satu yang menjadi isu terhambatnya pembangunan. Kemiskinan menjadi masalah sentral yang harus segera ditanggulangi dalam upaya mewujudkan tujuan nasional sebagaimana yang tercantum dalam Pembukaan Undang-undang Dasar 1945, yaitu melindungi segenap bangsa Indonesia dan seluruh tumpah darah Indonesia, memajukan kesejahteraan umum, mencerdaskan kehidupan bangsa dan ikut melaksanakan ketertiban dunia yang berdasarkan kemerdekaan, perdamaian abadi dan keadilan sosial. Metode penelitian yang digunakan adalah metode kualitatif. Pengumpulan data dilakukan dengan cara observasi, wawancara, dokumentasi, studi pustaka. Analisa data dilakukan dengan cara Reduksi data, Penyajian data, Menarik kesimpulan dan verifikasi Hasil penelitian dan pembahasan, Implementasi Peraturan Menteri Sosial Nomor 1 Tahun 2018 Tentang Program Keluarga Harapan (PKH) yang dilakukan di Kelurahan Talang Keramat Kecamatan Talang Kelapa Kabuapten Banyuasin sudah terlaksana dengan baik sebab komunikasi telah tercipta dengan baik, petugas pelaksana telah melaksanakan kewajiban dengan penuh tanggung jawab, struktur birokrasi yang ada juga sudah dapat dimengerti oleh masyarakat, adanya hal tersebut membuat pelaksanaan PKH menjadi efektif. Namun ada beberapa masalah yaitu pertama Kelurahan hanya sebagai fasilitaor, yang kedua belum ada dana anggaran yang diterima keluarahan dalam pelaksanaan PKH dan yang ketiga adalah pendataan yang tidak relevan dengan kehidupan masyarakat.